The preservation of cultural identity through the Gaelic athletic association in Finland : a case study of Helsinki Harps GAA - Jordan, Brian (2018)
There has always been a huge number of Irish emigrating and recently there has been a number of Gaelic Athletic Association (GAA) clubs founded throughout the world. This is not a new phenomenon, however the organisation’s growth in Eastern and mainland Europe is. This paper deals with the GAA in Finland and in particular Helsinki, due to the little research on this subject. The aim of this research is to determine if the Gaelic games can be used as a tool for preserving cultural identity for Irish immigrants. Also, what is the significance of the GAA abroad, and what is the connection between Irish national identity and the GAA. This research is valuable for GAA clubs in Ireland and abroad, sociologists, and emigrants abroad looking to preserve their cultural identity The research is guided by the qualitative case study research design. The data was collected by conducting five semi-structured interviews with people with deep and significant insights in Gaelic football in Helsinki, Finland. The interviewees were males aged 29 to 42 years old who are currently living in Helsinki, have done so for at least four years and are current members of the Helsinki Harps GAA club. The outcome highlighted how the GAA is a strong cultural identity link for Irish emigrants in Finland. The individuals can be seen to integrate bi-culturally into Finnish society, while maintaining their Irish culture. The chosen features from the theories used in the study supported the understanding of the individual’s experiences. All participants observed the significance of the GAA abroad for Irish citizens and the recognisable link between Ireland and the GAA. However, there are concerns with the future of the club and how well the club is integrating into Finnish society. The current research provides empirical weight to the participation of GAA outside of Ireland. The study recommends more funding for GAA clubs abroad, especially in development in children’s GAA and GAA events for all age groups. In addition, Helsinki Harps should introduce Finnish language and culture classes to the non-Finnish speaking members.